Paradoxical Internationalization: Regulatory Reforms in the Mexican Health‐Care System through the Lens of European Experience. Issue 4 (10th September 2018) - Bode, Ingo; Culebro M, Jorge E.
Abstract: Over the recent past, Mexico has been exemplary in having launched regulatory reforms in order to modernize its health‐care system, with major objectives being universal insurance coverage and less infrastructural fragmentation. In this article we argue that these reforms, widely inspired by the global New Public Management movement and its aftermath, take shape in a difficult encounter with both the traditional public administration model in Mexico and tensions endemic to the aforementioned reform movement as attempts to enhance system integration coincide with procedural disorganization. This results in a paradoxical internationalization of the Mexican health‐care system due to which the above objectives may be difficult to achieve. To illustrate our argument, we examine the Mexican case through the lens of experience two European countries (Germany and Norway) in which reforms have affected the health‐care system in a similar way.